Early Detection of Colon Cancer Following Incidental Finding of Bacteremia - Jasdeep Singh Sidhu MD; Amrendra Mandal MD; Jeevanjot Virk MD; Vijay Gayam MD (SAGE Publishing, 2019)
Clostridium septicum is a Gram-positive, anaerobic, spore-forming bacillus found in the intestine. It is linked to colon cancer and immunosuppression. Infection with C septicum may vary in manifestation and is associated with more than 60% mortality rate. In this article, we present a case of incidental isolation of C septicum in a patient who presented with fever and later on colonoscopy was found to have colon carcinoma. Bacteremia may be the unexpected initial presentation of undiagnosed colon carcinoma.